2014
DOI: 10.1063/1.4883502
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state for Eu-doped SrSi2O2N2

Abstract: α-SrSi2O2N2 is one of the recently studied oxonitridosilicates applicable in optoelectronics, in particular in white LEDs. Its elastic properties remain unknown. A survey of literature shows that, up to now, nine oxonitridosilicate materials have been identified. For most of these compounds, doped with rare earths and manganese, a luminescence has been reported at a wavelength characteristic for the given material; all together cover a broad spectral range. The present study focuses on the elastic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…However, experimental evidence 10,12,18,50 suggest that the substituted Eu 2+ atoms are randomly distributed across all substitution sites (may it be with uneven probability density). As already mentioned in Section 3.2, we attribute such random distribution of the Eu atoms substitution to the high firing temperature and the fact that Ba 2+ atoms form layers in BSON crystals.…”
Section: Additional Tests and Discussionmentioning
confidence: 99%
“…However, experimental evidence 10,12,18,50 suggest that the substituted Eu 2+ atoms are randomly distributed across all substitution sites (may it be with uneven probability density). As already mentioned in Section 3.2, we attribute such random distribution of the Eu atoms substitution to the high firing temperature and the fact that Ba 2+ atoms form layers in BSON crystals.…”
Section: Additional Tests and Discussionmentioning
confidence: 99%
“…We can see from this table that the differences among the bulk moduli of the three phases as well as the shear moduli are comparatively small, and all the bulk moduli for three phases are large. A comparison with bulk moduli of 103(5) GPa for SrSi 2 O 2 N 2 :Eu, which shows valuable luminescence properties, 33 suggests that CaAlSiN 3 might be a relatively hard material. In addition, we can see that B H is larger than G H , which implies that the shear moduli G H limit the stability of these phases.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…X-ray diffraction study of (Sr 0.98 Eu 0.02 )Si 2 O 2 N 2 under hydrostatic pressure has shown that in pressure range up to 96.5 kbar triclinic structure was conserved23. The main motivation on performing high hydrostatic pressure was to investigate whether high pressure influences the structural stability of (Sr 0.98-x Ba x Eu 0.02 )Si 2 O 2 N 2 (0 < x ≤ 0.98) to induce phase transitions.…”
mentioning
confidence: 99%